2010
DOI: 10.1007/s00221-010-2395-z
|View full text |Cite
|
Sign up to set email alerts
|

Improved detection following Neuro-Eye Therapy in patients with post-geniculate brain damage

Abstract: Damage to the optic radiation or the occipital cortex results in loss of vision in the contralateral visual field, termed partial cortical blindness or hemianopia. Previously, we have demonstrated that stimulation in the field defect using visual stimuli with optimal properties for blindsight detection can lead to increases in visual sensitivity within the blind field of a group of patients. The present study was aimed to extend the previous work by investigating the effect of positive feedback on recovery of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 36 publications
2
48
0
1
Order By: Relevance
“…Azzopardi & Cowey, 1998; P. Azzopardi & Cowey, 2001; Holmes, 1918; Perenin & Jeannerod, 1975; Pöppel, Held, & Frost, 1973; Riddoch, 1917; Weiskrantz, 1996; Weiskrantz, Barbur, & Sahraie, 1995; Weiskrantz, et al, 1974; Zeki & ffytche, 1998) - we and others have shown that it is possible to re-train both simple and complex visual discriminations in portions of the blind field using moving or flickering stimuli (Huxlin et al, 2009; Raninen, Vanni, Hyvärinen, & Näsänen, 2006; Sahraie et al, 2010; Sahraie et al, 2006). However, these findings raise many questions.…”
Section: Introductionmentioning
confidence: 84%
“…Azzopardi & Cowey, 1998; P. Azzopardi & Cowey, 2001; Holmes, 1918; Perenin & Jeannerod, 1975; Pöppel, Held, & Frost, 1973; Riddoch, 1917; Weiskrantz, 1996; Weiskrantz, Barbur, & Sahraie, 1995; Weiskrantz, et al, 1974; Zeki & ffytche, 1998) - we and others have shown that it is possible to re-train both simple and complex visual discriminations in portions of the blind field using moving or flickering stimuli (Huxlin et al, 2009; Raninen, Vanni, Hyvärinen, & Näsänen, 2006; Sahraie et al, 2010; Sahraie et al, 2006). However, these findings raise many questions.…”
Section: Introductionmentioning
confidence: 84%
“…Recent reports on animal models (19) and a human patient (20) with lesions extending to the lateral geniculate nucleus showed the absence of any residual visual processing within the field defect. However, in cases of postgeniculate lesions where some visual capacities are maintained, there is more likelihood of benefiting from rehabilitation techniques (21). Therefore, fast and effective screening for the presence of blindsight may be a useful and effective way of determining the probability of a successful rehabilitation outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on a number of cases with blindness after brain injury shows that repeated exposure to first-order stimuli over a period, using an experimental paradigm similar to those reported here, can lift performance from chance to well-above-chance levels, but without awareness (type I blindsight). Further systematic exposure to first-order stimuli over extended periods of time can result in type II performance (19,20). It would be of interest to investigate whether transition from type I to type II would be less likely with repeated stimulation with second-order stimuli.…”
Section: Discussionmentioning
confidence: 99%